Pathogenic Mechanisms of Bicuspid Aortic Valve Aortopathy - Yassine, Noor M.; Shahram, Jasmine T.; Body, Simon C. (Frontiers in Physiology, 2017)
Bicuspid aortic valve (BAV) is the most common congenital valvular defect and is associated with ascending aortic dilation (AAD) in a quarter of patients. AAD has been ascribed to both to the hemodynamic consequences of normally- functioning and abnormal BAV morphology, and to the effect of rare and common genetic variation upon function of the ascending aortic media. AAD takes manifests in two overall and sometimes overlapping phenotypes: – that of aortic root aneurysm, similar to the AAD of Marfan syndrome; ;, and that of tubular aortic root aneurysmtubular AAD, similar to the AAD seen with tricuspid aortic valves. These aortic phenotypes appear to be unrelated independent ofto BAV phenotype, have different embryologic origins and seem to have unique etiologic factors; , notably, for regarding the role of hemodynamic changes inherent to the BAV phenotype. Further, in contrast to Marfan syndrome, the AAD seen with BAV AAD is infrequently present as a strongly- inherited syndromic phenotype unlike Marfan syndrome; rather, it appears to be a poorly less-penetrant, milder phenotype. Both r that may be due to reduced levels of normally functioning cellular transcriptional proteins of smooth muscle cells, or structural proteins of the aortic media extracellular matrixand structurally abnormal proteins have been observed in aneurysmal aortic media. We propose an overall thesis thatprovide evidence that aortic root AAD has a stronger genetic etiology, perhaps sometimes related to identified common non-coding fibrillin-1 (FBN1) variants and other aortic wall protein variants that are associated with AAD in patients with tricuspid and bicuspid aortic valvesBAV. In patients with BAV patients withhaving tubular AAD, we propose a stronger hemodynamic influence, but with pathology still based on a functional deficit of the aortic media, of genetic or epigenetic etiology. Although it is an attractive hypothesis to ascribe common mechanisms to BAV and AAD, are likely tthus far the genetic etiologies of AAD have not been associated to the genetic etiologies of BAV, notably, from not including variants in NOTCH1 and GATA4.